2017
DOI: 10.1002/slct.201701352
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Paper Strips for Highly Sensitive and Selective Detection of Nitroaromatic Analytes in Water Samples

Abstract: A portable, low-cost, flexible, sensitive and selective paperbased sensor was proposed for nitroaromatic explosive detection in water samples. The sensor was designed to achieve p-p stacking formation between emaraldine base polyaniline (PANI) and pyrene (Py) molecules. This p-p stacking formation enables a sensitive turn-off fluorescence quenching under the principle of photo-induced electron transfer (PET) mechanism. PANIÀPy absorbed paper strips were immersed into the aqueous mediums of analytes and the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The quenching of fluorescence of the aggregated probe by NAC explosives may arise through the PET mechanism (Scheme S2). 41 The quenching efficiency (%) of the aggregated fluorescence (λ em , 540 nm; v/v, 9:1 H 2 O/MeOH) of H-PNAP (50 μM) upon addition of different NACs with different concentrations is also checked, and it shows that among all the NACs, only TNP and DNP show the highest quenching efficiency around 95 and 92%, respectively (Figure 7).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quenching of fluorescence of the aggregated probe by NAC explosives may arise through the PET mechanism (Scheme S2). 41 The quenching efficiency (%) of the aggregated fluorescence (λ em , 540 nm; v/v, 9:1 H 2 O/MeOH) of H-PNAP (50 μM) upon addition of different NACs with different concentrations is also checked, and it shows that among all the NACs, only TNP and DNP show the highest quenching efficiency around 95 and 92%, respectively (Figure 7).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The reversibility of the highly emissive aggregated probe, H-PNAP (90% water/MeOH), is ). 41 The quenching efficiency (%) of the aggregated fluorescence (λ em , 540 nm; v/v, 9:1 H 2 O/MeOH) of H-PNAP (50 μM) upon addition of different NACs with different concentrations is also checked, and it shows that among all the NACs, only TNP and DNP show the highest quenching efficiency around 95 and 92%, respectively (Figure 7). Upon gradual addition of the TNP/DNP solution (0.01 mL × 10 −3 M) to aggregated H-PNAP (90% water/MeOH), the emission intensity gradually decreases (Figure S13).…”
Section: Acs Omegamentioning
confidence: 99%
“…Development of selective, sensitive, portable and cost effective sensors for the detection of nitro explosive has attracted great interest in researchers in recent years.In a review by S. Pandey and his subsequent reports the application of Polyaniline and its composites for sensing NH 3 , H 2 , HCl, NO 2 , H 2 S, CO, CO 2 , SO 2 , LPG, has been discussed comprehensively.Nitroaromatics (NACs) are powerful explosives and also toxic pollutants and their detection is a great concern due to national security, industrial and environmental protection . Among various NACs trinitrotoluene (TNT), dinitrotoluene (DNT) and trinitro phenols (TNP) / picric acid (PA) are important constituents of industrial explosives.…”
Section: Introductionmentioning
confidence: 99%
“…Since the turn off response was so evident in the solution, a portable inexpensive paper-based solid sensor was explored. Other studies have shown that fluorescent paper strips can be developed to have high selectivity and sensitivity towards nitroaromatic pollutants due to π-π stacking [39]. In this study, a paper-based sensor approach was explored for accelerating the turn off fluorescence quenching of NaFl in the presence of nitroaromatic pollutants.…”
Section: As Indicated In Tablementioning
confidence: 99%